Parthenolide Inhibits IκB Kinase, NF-κB Activation, and Inflammatory Response in Cystic Fibrosis Cells and Mice - Saadane, Aicha (American Thoracic Society, 2007)
Cystic fibrosis (CF) is characterized by prolonged and excessive inflammatory responses in the lung and increased activation of NF-κB. Parthenolide is a sesquiterpene lactone derived from the plant feverfew, which has been used in folk medicine for anti-inflammatory activity. Several studies suggest that this compound inhibits the NF-κB pathway, but the exact site is controversial. We hypothesized that parthenolide might ameliorate the excessive inflammatory response in CF models by inhibiting activation of NF-κB. This was tested in vitro, using two pairs of cell lines with defective versus normal CF transmembrane conductance regulator (CFTR) (antisense/sense transfected 16 HBE and IB-3/S9), and in vivo, using CFTR-knockout (KO) mice. All cell lines were pretreated with parthenolide and then stimulated with IL-1β and/or TNF. Parthenolide significantly inhibited IL-8 secretion induced by these cytokines and prevented NF-κB activation, IκBα degradation, and IκB Kinase complex activity. CFTR-KO and wild-type mice were pretreated with parthenolide or vehicle alone then challenged intratracheally with LPS. Bronchoalveolar lavage was performed 3, 6, and 8 h later. Parthenolide pretreatment inhibited PMN influx as well as cytokine and chemokine production. This was also associated with inhibition of IκBα degradation and NF-κB activation. We thus conclude that parthenolide inhibits IκB kinase, resulting in stabilization of cytoplasmic IκBα, which in turn leads to inhibition of NF-κB translocation and attenuation of subsequent inflammatory responses. IκB kinase may be a good target, and parthenolide and/or feverfew might be promising treatments for the excessive inflammation in CF.